2011
DOI: 10.4489/kjm.2011.39.1.016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Korean Cylindrocarpon destructans Based on Virulence Aassay and RAPD Analysis

Abstract: : Ginseng root rot caused by Cylindrocarpon destructans is one of the most destructive diseases of ginseng (Panax ginseng). We analyzed the features of the species through pathogenicity test and genetic diversity analysis of C. destructans in Korea, for its application as basic data to attempt for effective control. C. destructans isolated from rotted ginseng roots exhibited a variety of colonial colors on media. It was assumed that there may exist genetic diversity in the population by the diversity of pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[ 11 ]. Genetic diversity of C. destructans from Asian ginseng in Korean has been associated with hosts based on RAPD finger printing or sequence analysis of nuclear ribosomal gene internal transcribed spacer (ITS) and mitochondrial small subunit (mt SSU) rDNA; however, in the study, only less than 20 isolates were investigated [ 12 , 13 ]. Although there are no genetic markers employed specifically in genetic study of CLF, several phylogenetic analyses of CLF showed that histone H3 ( his3 ) gene had the highest resolution among several gene loci [ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ]. Genetic diversity of C. destructans from Asian ginseng in Korean has been associated with hosts based on RAPD finger printing or sequence analysis of nuclear ribosomal gene internal transcribed spacer (ITS) and mitochondrial small subunit (mt SSU) rDNA; however, in the study, only less than 20 isolates were investigated [ 12 , 13 ]. Although there are no genetic markers employed specifically in genetic study of CLF, several phylogenetic analyses of CLF showed that histone H3 ( his3 ) gene had the highest resolution among several gene loci [ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several attempts have been made to establish a new type of classification system for the Nectria / Neonectria complex and to analyze the genetic diversity using various morphological, pathogenic, and genetic analytical approaches [ 9 , 17 , 18 , 19 ]. Although the genetic variation of Korean C. destructans population that causes root rot in P. ginseng has been evaluated by random amplified polymorphic DNA analysis [ 20 , 21 ], the pathogenic and taxonomical characteristics of P. ginseng in Korea have been rarely studied. As the genetically distinct populations may show difference in host range, aggressiveness, and susceptibility to disease control treatment, a better understanding of the genetic and pathogenic variations in C. destructans will be important for developing suitable root rot disease management strategies [ 16 ].…”
mentioning
confidence: 99%